2004
DOI: 10.1088/0953-8984/16/12/006
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric anomalies and phase transition in glycinium phosphite crystal under the influence of a transverse electric field

Abstract: The dielectric properties of glycinium phosphite (GPI) crystals as a function of temperature and electric field magnitude are investigated. The electric field E is applied perpendicularly to the ferroelectric b-axis in the direction of hydrogen-bonded phosphite chains in the crystal (the c-axis). The shift of the paraelectric–ferroelectric phase transition to lower temperatures proportionally to Ec2 (where Ec is an effective field in the sample) is observed. Strong anomalies in the field dependence of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…Analogous results were obtained in [48,50] in their studies of the transverse electric field dependence of the transverse dielectric susceptibility of glycinium phosphite.…”
supporting
confidence: 75%
“…Analogous results were obtained in [48,50] in their studies of the transverse electric field dependence of the transverse dielectric susceptibility of glycinium phosphite.…”
supporting
confidence: 75%
“…It is shown that the dependences T c (E 1,3 ) are close to quadratic in the fields (see [10]), and at the fields up to 4 MV/m, they can be written as: With an increase of strength of the electric field E 1 , the spontaneous polarization P 2 slightly decreases, but polarization P 1 induced by the field increases. Polarization P 3 induced by the field E 1 is negative, and in magnitude it is three times larger than the P 1 .…”
Section: Comparison With the Experimental Datamentioning
confidence: 94%
“…The results of an experimental investigation of the static dielectric permittivity ε 33 of GPI crystal at different values of the field E 3 are presented in [10,11]. The phase transition temperature for this case was 222 K, but the field dependence of the T c is similar to the crystal with T c = 225 K. Therefore, having made the above mentioned changes of the model parameters, we consider it possible to explain the experimental data.…”
Section: Comparison With the Experimental Datamentioning
confidence: 95%
“…The experiment, carried out in [34], revealed anomalies of permittivity ε zz in the phase transition region at E z 0 and a decrease of the phase transition temperature proportional to E 2 z . For the first time, the explanation of the revealed effects was given on the basis of phenomenologic theory [35] and within microscopic approach [34,36]. Unfortunately, a complete quantitative description of these experimental data was not obtained.…”
Section: Introductionmentioning
confidence: 99%